ISLAM DAN DEMOKRASI: Analisis Komparatif Persamaan Prinsip Demokrasi dan Prinsip Pemerintahan Islam dalam Perspektif Al-Qur’an - Hanan, Abdul; Mujiono, Mujiono; Mukroni, Mukroni; Khasanah, Uswatun (Moderation | Journal of Islamic Studies Review, 2025)
Democracy, as a system of governance, emphasizes the participation of the people through their representatives, reflecting values of equality and justice. In the Islamic context, governance principles include justice, consultation, and trustworthiness, all aimed at achieving societal welfare. This research employs a qualitative descriptive method to analyze the similarities between the principles of democracy and Islamic governance based on the Qur'an. The findings indicate that the recognition and protection of human rights, as well as obedience to leaders, are essential aspects of both systems. Thus, democracy and Islamic governance can complement each other in creating a just and prosperous society.